A Novel Antifouling RO Polyamide/Myrrh Membrane for Waste Water Purification - N. F. Alotaibi; M. A. Alsolami; Shaima M. N. Moustafa; Nawaf Bin Darwish; A. M. Nassar (Adsorption Science & Technology)
In the present work, desalination of real samples from Dumat Al-Jandal Lake water (located in Jouf region) was carried out via reverse osmosis (RO) technique. The growth of bacteria on the surface of RO membrane is an essential issue of this method. It creates defects in membrane properties as salt rejection and preparation. Many approaches have been proposed to prevent the growth of bacteria on membrane. The addition of some materials such as natural products was one of those approaches. In this work, myrrh was chosen because it is well known as an antibacterial natural product. Unmodified RO membrane was prepared in the lab using interfacial polymerization between trimesoyl chloride (TMC, 0.1 M) and m-phenylenediamine (MPD, 0.3 M). The characterization was obtained by using infrared (IR) and scanning electron microscopy (SEM). The properties of RO membrane as water flux and salt rejection were determined using lake water. The obtained results were 25 and 65% for water flux and salt rejection, respectively. In respect of modified RO membrane, myrrh solution with different concentrations was prepared and mixed with membrane materials. The modified membrane was characterized with IR and SEM. Water flux and salt rejection were determined obtaining results of 42 and 41% for water flux and salt rejection, respectively. The resistance of bacterial growth was tested for both modified and unmodified membranes, showing that the modified membrane presented high resistance of bacterial growth in contrast to the unmodified one.